The two-state impasse in Israel/Palestine—The EU caught between egalitarian norms and expansionist realpolitik - Strömbom, Lisa; Persson, Anders (Frontiers in Political Science, 2023)
In recent years, many academics as well as local actors have started to question the feasibility of a two-state solution for Israel and Palestine. Increased Israeli unilateralism, expansionism as well as weak Palestinian institutions have instead pointed toward a “one-state-reality” where Israel is in de facto control over all lands. This in turn reveals a paradox, where international policymakers, most prominently in the EU and the US, and international organizations like the UN, seem determined to insist on a two-state solution, even though all facts on the ground indicate a move away from such a vision where the egalitarian principles inherent in the two-state solution exists in constant tension with expansionist attempts to establish Israeli sovereignty also on Palestinian land. This article unpacks various visions for the future in Israel-Palestine, based on egalitarian principles on the one hand and expansionist ones on the other and display how they current co-exist in a very uneasy relationship. The over-arching aim of the article is to understand how the EU relates to this paradox. We do this in three steps; first we conduct a mapping of visions for solving the Israeli-Palestinian conflict according to either egalitarian or expansionist principles, where we find one- as well as two-state solutions; second, we conduct a historical analysis on EU positions with regards to the abovementioned principles for solving the conflict, related to other powerful international actors' visions; lastly, we move to an investigation of current developments captured through recent speeches, documents and semi-structured interviews with centrally placed EU staff. Our main conclusion is that even though the EU is determined to hold on to the two state-solution, it however lacks willingness and/or power-resources to push Israel in that direction. Our interviewees seem painfully aware of the lack of viability of the two-state-solution and hence welcome criticism which could push for more egalitarian tendencies in Israel by appealing to its democratic-self-image. Here the current spread of the apartheid narrative among international organizations and an increased international human rights rhetoric emphasizing equal rights for two peoples seem to have left the EU balancing on a tight-rope where they have to choose between standing by status quo, risking supporting ultra-nationalist Israeli sovereignty-aspirations, or criticizing those, instead exposing itself to accusations of antisemitism.